POSSIBILITY OF USING UNMANNED AERIAL VEHICLES FOR INSPECTION OF OIL AND GAS PIPELINES - Kozlov, Vladimir Viktorovich; Volyanska, Larysa Georgievna; Otroschenko, Volodymyr (Science-based technologies, 2021)
The article considers the possibilities of using unmanned aerial vehicles for monitoring the main pipelines of the gas transmission system.